Assisting Children with Autism Spectrum Disorder with Educational Mobile Apps to Acquire Language and Communication Skills: A Review - Hussain, Azham; Mkpojiogu, Emmanuel O.C; Okoroafor, Pauline Chiamaka (International Journal of Interactive Mobile Technologies (iJIM), 2021)
This systematic literature review was set out to review available literature on autism spectrum disorder and educational mobile apps with the aim of investigating available educational mobile app and how teachers can utilize these apps in assisting autistic children in acquiring language and communication skills. In order to achieve the aim of the study, the researchers employed a systematic method of investigation. Fifty papers in the areas of autism, educational apps and teaching method for autistic children were downloaded. Twenty-six were carefully selected because of their relevance to the study. The papers were analyzed and the result showed that there are available educational apps that are effective in helping autistic children in acquiring language and communication skills.